Role of Ultrasonographic Measurement of Fetal Head Circumference in the Evaluation of Gestational age in Bangladeshi Women - Sharma, Netay Kumer; Dey, Sankar Narayan; Rahman, Md Masudur; Zahan, Akter; Islam, Mahzabeen; Mukthadira, - (Community Based Medical Journal, 2017)
Determination of gestational age by ultrasound has now become an integral part of maternal antenatal care. Accurate assessment of gestational age by sonography is now essential for obstetric management particularly due to term, preterm and post date management. Timing of elective caesarean delivery and decision whether to consider a fetus at risk for intrauterine growth retardation depends in part on the estimated age. In this study gestational age was determined on the basis of head circumference (HC) and correlation was established between weeks of gestation calculated from LMP. A cross sectional study was carried out in the department of Radiology & Imaging, Mymensingh Medical College Hospital during the period of January 2011 to June 2012. Three hundred ninety seven normal pregnant Bangladeshi women age range from 20 to 36 years with apparently healthy fetuses between 18 to 38 weeks of gestation referred for ultrasonic evaluation of pregnancy profile. Mean age was 29.60 years with standard deviation (SD) +0.67. Aim of this study was to determine relationship between menstrual age and HC. Result of this study may give idea about gestational age calculated by LMP of 397 cases and expressed in weeks. Estimated gestational age was determined by HC evaluated by US and expressed in weeks. Significant positive correlation was found between gestational age measured by HC and LMP. Estimated gestational age measured by HC had very close relation with weeks of gestation(LMP), which is 2 to 3 days less from weeks of gestation (LMP) during 18-38 weeks of gestation variation was only 2 to 4 days less from weeks of gestation (LMP). A strong positive significant correlation (r=0.987, P<0.001) was found between weeks of gestation and predicted gestational age measured from HC. Significant relationship between gestational age measured by LMP with estimated gestational age evaluated by head circumference. CBMJ 2017 July: Vol. 06 No. 02 P: 06-11